A new approach for irregular porous structure modeling based on centroidal Voronoi tessellation and B-spline. Issue 4 (3rd July 2016) - You, Y.H.; Kou, S.T.; Tan, S.T.
ABSTRACT: In this paper, we introduce a new approach for irregular porous structure modeling based on centroidal Voronoi tessellation (CVT) and B-Spline. Given an arbitrary domain, a CVT is first constructed on it, decomposing the domain into a set of Voronoi cells. A scaled Voronoi cell is then generated within each Voronoi cell of the CVT with respect to a unique scale factor. Finally, a pore is generated in each Voronoi cell by using B-Spline with the vertices of each scaled Voronoi cell being the control points. Compared to existing approaches, the proposed method is much more flexible to control the pore size and distribution both globally and locally. In addition, our method can effectively prevent overly large or small angles within Voronoi cells, which are the source of simulation errors and computational burdens in finite element analysis (FEA). GRAPHICAL ABSTRACT: